The role of Cdk5 in neurological disorders - Ao, Chuncao; Li, Chenchen; Chen, Jinlun; Tan, Jieqiong; Zeng, Liuwang (Frontiers in Cellular Neuroscience, 2022)
Neurological disorders are a group of disorders with motor, sensory or cognitive damage, caused by dysfunction of the central or peripheral nervous system. Cyclin-dependent kinases 5 (Cdk5) is of vital significance for the development of the nervous system, including the migration and differentiation of neurons, the formation of synapses, and axon regeneration. However, when the nervous system is subject to pathological stimulation, aberrant activation of Cdk5 will induce abnormal phosphorylation of a variety of substrates, resulting in a cascade signaling pathway, and thus lead to pathological changes. Cdk5 is intimately related to the pathological mechanism of a variety of neurological disorders, such as A-β protein formation in Alzheimer’s disease, mitochondrial fragmentation in cerebral ischemia, and apoptosis of dopaminergic neurons in Parkinson’s disease. It is worth noting that Cdk5 inhibitors have been reported to have neuroprotective effects by inhibiting related pathological processes. Therefore, in this review, we will briefly introduce the physiological and pathological mechanisms of Cdk5 in the nervous system, focusing on the recent advances of Cdk5 in neurological disorders and the prospect of targeted Cdk5 for the treatment of neurological disorders.